Arah Baru bagi Insan JPKM: Merangkul Relevansi Internasional dan Nasional - Nido Dipo Wardana (Airlangga University Press, Universitas Airlangga, 2022)
English has become the lingua franca in scientific communication. Non-native researchers were even found to submit 60% of their manuscripts in English (Stockemer & Wigginton, 2019). A belief that English publications can increase the reputation of the authors was known as the primary motivation behind this publication preference. Indeed, English articles tend to obtain a higher number of citations (Di Bitetti & Ferreras, 2017). This might be because English renders publications accessible to more readers. Many institutional bodies (including universities) eventually encourage their researchers to publish their works exclusively in English (Márquez & Porras, 2020).